Splenic protection network revealed by transcriptome analysis in inactivated vaccine-immunized flounder (Paralichthys olivaceus) against Edwardsiella tarda infection - Xiaoyan Wu; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Frontiers in Immunology, 2022)
The protective immune response produced by fish after vaccination is crucial for vaccine effectiveness. Our previous studies have shown inactivated vaccine against Edwardsiella tarda can induce immune response in flounder (Paralichthys olivaceus). To elucidate the protective immune response at the genetic level, in this study, flounder was immunized with inactivated E. tarda for 5 weeks, and then they were challenged with E. tarda. The spleen was dissected at 7th day post immunization, 1st and 7th day post challenge, respectively. Transcriptome analysis showed that average of 46 million clean reads were obtained per library, while percentage of clean reads being mapped to reference genome was more than 89% in all cases, which suggested good quality of samples. As for differentially expressed genes (DEGs) identification in inactivated E. tarda groups, at 7th day post immunization, 1422 DEGs were identified and significantly enriched in innate immune-related pathways, such as Phagosome, Cell adhesion molecules and NF-kappa B signaling pathway; At 1st post challenge day, 1210 DEGs were identified and enriched to Antigen processing and presentation and Cell adhesion molecules, indicating that the pathogen was rapidly recognized and delivered; At 7th post challenge day, 1929 DEGs were identified, belonged to Toll-like receptor signaling pathway, Antigen processing and presentation, Th1 and Th2 cell differentiation and Th17 cell differentiation. Compared to 7th post immunization day, 73 immune-associated DEGs were identified at 1st post challenge day. Protein-protein interaction networks analysis revealed 11 hub genes (TLR7, TLR3, CXCR4, IFIH1, TLR8 etc), associated with recognition of pathogens and activation of innate immunity; while for 7th post challenge day, 141 immune-associated DEGs were identified. 30 hub genes (IL6, STAT1, HSP90A.1, TLR7, IL12β etc) were associated with stimulation of lymphocyte differentiation and activation of cellular immunity. Ten immune-related genes were randomly selected for RT-qPCR validation at each time point. In conclusion, data revealed protection of flounder against E. tarda infection by inactivated vaccine is mediated via immediate recognition of pathogen and subsequently activation of cellular immunity. Results give new aspect for vaccine protection cascades, is good references for vaccine evaluation.